HUBUNGAN ANTARA KONTROL SOSIAL ORANGTUA DENGAN KENAKALAN REMAJA DI KOMPLEK MEGA PERMAI V KELURAHAN LUBUK BUAYA KOTA PADANG - Afif Perdana; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
ABSTRACTThis research was motivated by the high level of juvenile delinquency in the Mega Permai V Complex, Lubuk Buaya Village, Padang. This can be caused by many factors including the low parental social control. This study aims to see a picture of parental social control, a picture of juvenile delinquency and the relationship between juvenile delinquency in Mega Permai V Complex, Lubuk Buaya Village, Padang. This type of research is descriptive correlational where parental social control is a variable (X) and juvenile delinquency as a variable (Y). The population in this study were 55 people. The sampling technique used was simple random sampling technique as many as 35 people. Data collection techniques used were questionnaires and data collection tools in the form of questionnaires. Meanwhile, the data analysis technique uses the percentage formula and the product moment. The results showed that the description of parental social control to adolescents was still categorized as low, the description of juvenile delinquency was categorized as high and there was a significant relationship between juvenile delinquency in Mega Permai V Complex, Lubuk Buaya Village, Padang.Keywords: Parental social control, juvenile delinquency